Minimally Invasive Stabilization with Percutaneous Screws Fixation of APC-3 Pelvic Ring Injury - Beom-Soo Kim; Jong-Keon Oh; Jae-Woo Cho; Do-Hyun Yeo; Jun-Min Cho (Journal of Trauma and Injury)
Pelvic fractures are associated with life-threatening injuries and high rates of morbidity and mortality. Management of internal blood loss associated with unstable pelvic ring injuries is paramount during the initial period. The reconstruction of the pelvic ring is of importance because it is a major contributor to the stability of the pelvic ring. We report the case of a 25-year-old man who had an unstable pelvic ring fracture combined with rupture of an obturator artery and had a successful and satisfactory treatment using minimally invasive surgery with percutaneous antegrade screw fixation.